Green Servicescape and Impulse Buying Behavior: The Mediating Role of Positive Emotion - Risnawati Risnawati; Maududi Lamparawi Magenda; Syahriah Sari; Tri Wahyu Septyani (PINISI Discretion Review, 2026)
The second-hand fashion market has experienced fluctuating trends over the years and has been accompanied by increasing impulse buying tendencies, particularly among young consumers visiting second-hand clothing stores. Impulse buying is no longer solely influenced by economic motives but is increasingly shaped by shopping experiences and service environments. This study aims to examine the effect of green servicescape on impulse buying through the mediating role of positive emotion. The green servicescape construct consists of three dimensions: environmental concern, atmosphere, and human. This study employed an explanatory research design involving customers of second-hand clothing stores in Makassar City. A total of 267 respondents were selected using purposive sampling techniques, and the data were analyzed using WarpPLS 7.0. The results indicate that green servicescape positively affects positive emotion, which subsequently influences impulse buying. Furthermore, positive emotion mediates the relationship between green servicescape and impulse buying. These findings highlight the importance of sustainability-oriented service environments in shaping consumers’ emotional experiences and influencing impulse buying in the second-hand fashion market.